The Design of Consumer Legal Protection Arrangements in Indonesia Based on Artificial Intelligence - Suharyono, Suharyono; Hayatuddin, Khalisah; Is, Muhamad Sadi; Sobandi, Sobandi (Universitas Islam Sultan Agung, 2024)
The consumer protection in Indonesia from year-to-year increased weakness, based on the data from the Ministry of Industry and Trade of the Republic of Indonesia that the percentage of consumer complaint services in 2022 increased by 93%. Then, the data from the Indonesian Consumers Foundation (YLKI) in 2022 received 882 consumer complaints in Indonesia. This number increased by 64.86% compared to 2021 with 535 complaints. This article aimed to identify and analyse how to design legal protection arrangements for consumers in Indonesia based on Artificial Intelligence (AI). The results of the study showed that the design of legal protection arrangements for consumers in Indonesia was based on Artificial Intelligence (AI), by revising the Law No. 8 of 1999 concerning Consumer Protection, by including articles that accommodated Artificial Intelligence in legal protection of consumers in Indonesia, both carried out by the Indonesian Consumers Foundation (YLKI) and by the Consumer Dispute Settlement Agency (BPSK), which guaranteed fairness, certainty and benefits for both consumers and for business actors in Indonesia.